Manifest - Piero Coda (Diakrisis, 2020)
Edgar Morin writes that “rethinking thinking” is what is urgently needed today. Indeed, it is possible to recognize a convergence in the understanding and practice of an integral and open ontology express and promote the living mystery of Being in its multicolored self-expression. This fact calls for a rereading of the tradition of thought, which has matured through history leading to this point. In this perspective, the most significant fruit was produced by the inventio of the ontologically regulating concept of God-Trinity as the interpretive key for the coming in human flesh of the Word/Son Who is God Himself. However, the concept of Trinity failed to completely generate that locus of experience and that relational and communitarian practice of thought corresponding to the Reality it had received and conceived. Our working hypothesis is that philosophy and theology can find the place again for a rebirth and reconfiguration of ontology in the guiding thought of the Trinity, taken up in its original irradiating meaning with the focus on the Christ’s cross/resurrection and examined in the still unfathomed promise it contains.